Simplify

- 3/4 r + 3 - 5/6r - 6

1 answer

To simplify the expression, we can combine like terms:

- (3/4) r - (5/6) r + 3 - 6

First, let's simplify the r terms:

- (18/24) r - (20/24) r

This can be simplified to:

- (18 - 20)/24 r

Which becomes:

- (-2)/24 r

Now, let's simplify the constant terms:

3 - 6 = -3

Now we can combine the simplified terms:

- (-2)/24 r - 3

This can be further simplified by dividing both the numerator and denominator of the fraction by 2:

- (-1)/12 r - 3

Therefore, the simplified expression is - (1/12) r - 3.
Similar Questions
  1. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  2. Simplify 8a − 2a.Simplify 12e − 5f − 7e +3f. Simplify 9x + 3y − 6 − 5x + 4y −3. Simplify 9/11z − 4/11z. Simplify
    1. answers icon 4 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
  4. So I need some help on these Graphing Square Root Functions Quiz questions.1. Simplify 2 over √5 2. Simplify -11√112 3.
    1. answers icon 1 answer
more similar questions